2008
DOI: 10.2217/14796678.5.1.93
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen, Aging and the Cardiovascular System

Abstract: Estrogen is a powerful hormone with pleiotropic effects. Estrogens have potent antioxidant effects and are able to reduce inflammation, induce vasorelaxation and alter gene expression in both the vasculature and the heart. Estrogen treatment of cultured cardiac myocytes and endothelial cells rapidly activates NFκB, induces heat-shock protein (HSP)-72, a potent intracellular protective protein, and protects cells from simulated ischemia. In in vivo models, estrogens protect against ischemia and trauma/hemorrhag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
35
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 89 publications
(97 reference statements)
2
35
0
2
Order By: Relevance
“…Stice et al asserted that estrogen played roles on protection cardiovascular system from ischemia by activating NFB, inducing heat-shock protein (hsp)-72 and decreasing the expression of soluble epoxide hydrolase [53]. Estradiol also reported to promote the association of hsp-90 with endothelial nitric oxide synthase and reduce the Ca2+ requirement for its activation [54].…”
Section: Discussionmentioning
confidence: 99%
“…Stice et al asserted that estrogen played roles on protection cardiovascular system from ischemia by activating NFB, inducing heat-shock protein (hsp)-72 and decreasing the expression of soluble epoxide hydrolase [53]. Estradiol also reported to promote the association of hsp-90 with endothelial nitric oxide synthase and reduce the Ca2+ requirement for its activation [54].…”
Section: Discussionmentioning
confidence: 99%
“…The increasing realization that early life events can have manifold later life health impacts make the examination of early life hormonal profiles of particular interest (Bartke et al, 2016; Brakefield et al, 2005; Sonntag et al, 2005). Assuming that the survival advantage is fairly general to female mammals (something that is still unknown), then the anti-oxidant (Mann et al, 2007; Stice et al, 2009) and anti-inflammatory (Benedusi et al, 2012; Villa et al, 2015) properties of estrogen seem like one obvious place to look for an explanation. Both oxidative damage and chronic low-grade inflammatory activation in later life have been implicated in aging (Barja, 2004; Finch, 2007; Ku and Sohal, 1993).…”
Section: Mechanisms Of Sex Differences In Longevitymentioning
confidence: 99%
“…In addition to the well-established functions of estrogens in female reproduction, studies demonstrated significant non-reproductive functions of estrogens in the regulation of lipid and carbohydrate metabolism, skeletal homeostasis, the cardiovascular system, and the central nervous system (CNS) in both males and females [23; 24; 25; 26; 27; 28; 29]. …”
Section: Introductionmentioning
confidence: 99%